แนวทางการเสริมพลังให้กับคนคุ้ยขยะที่หลุมฝังกลบเพื่อขับเคลื่อนแนวคิดเศรษฐกิจหมุนเวียน กรณีศึกษา: ศูนย์กำจัดมูลฝอย องค์การบริหารส่วนจังหวัดนนทบุรี - จิราภรณ์ จันทร์แย้ม (เครือข่ายส่งเสริมงานวิชาการทางสังคมศาสตร์, 2022)
The objectives of this research are: to study the local waste pickers’ way of life and how they select plastic wastes at Waste Disposal Center, Nonthaburi Provincial Administrative Organization, and to make suggestions on improving their quality of life through a circular economy promotion. A qualitative research was used by collecting data from in-depth interviews and non-participant observations. The interviewees were operational officers from Resources and Environment Division, Nonthaburi Provincial Administrative Organization, and a group of people collecting antiques for sale. The results showed that the group of people collecting waste for sale started working at the waste landfill sites in the morning and finished their work in the evening. They spent the daily life there: resting, having meal, and sorting garbage. They had small sheds, protecting them from the sun and rain. In terms of quality of life, the waste pickers were lacking of education opportunities, welfare access, and basic life supports. They were working in the same way every day by sorting wastes into the types of plastics. Also, they did not have some necessary knowledge to increase their income. There is still a small number of business developments related to circular economy in the area due to limited resources and knowledge. Therefore, the action plan is to develop the waste pickers’ recycling skills with professional standard, so that they become on-site professional recyclers. This action plan from the solid waste disposal center is to increase income for recyclers, and to gain more income from plastic waste management by the transforming process, while also reducing the amount of plastic waste and limited landfill.